2010
DOI: 10.1111/j.1743-6109.2009.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean Red Ginseng on Sexual Arousal in Menopausal Women: Placebo-Controlled, Double-Blind Crossover Clinical Study

Abstract: Introduction Many menopausal women experience climacteric symptoms including impairment of sexual function. Recent reports have suggested that Korean red ginseng (KRG) has a relaxing effect on the clitoral cavernosal muscle and vaginal smooth muscle in rats. Aim We assessed whether KRG extracts would improve sexual function in menopausal women. Methods Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 42 publications
2
83
1
1
Order By: Relevance
“…KRG has been demonstrated to be effective in numerous vascular diseases [23][24][25][26][27][28][29][30][31][32][33][34]. The authors believed that KRG supplementation in open-angle glaucoma patients might be helpful for improving ocular blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KRG has been demonstrated to be effective in numerous vascular diseases [23][24][25][26][27][28][29][30][31][32][33][34]. The authors believed that KRG supplementation in open-angle glaucoma patients might be helpful for improving ocular blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Red ginseng is reported to be pharmacologically more active than raw ginseng in terms of chemical constituents (Rh4 and Rf2) that are produced in the steaming process [22]. In the past few years, the favorable effects of Korean red ginseng (KRG) have been reported in numerous diseases, including cardiovascular disease [23][24][25][26][27][28], cerebrovascular disease [29], hyperlipidemic disease [30,31], sexual dysfunction [32,33], and Alzheimer's disease [34], though the exact explanation for these effects is not clear.…”
mentioning
confidence: 99%
“…Ginseng has been used in Asian countries to promote several health aspects, including sexual function, rarely having any adverse effects. 21 Several studies have described the clinical efficacy of ginseng and its extract for treatment of ED. 20,22 However, Jang et al 23 reported that out of 28 published articles on the effect of ginseng on the treatment of ED, only 7 articles satisfied their strict criteria of being double-blind, placebo-controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of these studies did not describe baseline comparison of ED symptoms or obtain appropriate ethical approval. [20][21][22][23][24] The clinical trial described herein was designed as a multicenter, randomized, double-blind, placebo-controlled study, addressing both the efficacy and safety of SKGB extract in men with mild-to-moderate ED.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study, the effect of Korean Red Ginseng (KRG) extract on improving sexual function was assessed in 28 menopausal women (51.2 ± 4.1 years old) with a mean menopausal duration of 37.4 ± 2.9 months (Oh et al, 2010). The result was that KRG extract significantly improved scores on the Female Sexual Function Index in the sexual arousal domain (Oh et al, 2010).…”
Section: Sexual Arousal In Menopausal Womenmentioning
confidence: 97%